Seismic Response and Economic Study of New Light Steel-Wood-Plastic Structure in Rural Yunnan, China - Shujiang Jiang; Jie Yang; Dewen Liu; Jingran Xu; Zhiang Li; Liang Gao; Yutong Yang; Bingxing Ma (Geofluids)
A new type of light steel-wood-plastic residential structure in rural has popular in recent years in rural Yunnan, China. The application of light steel, wood, and new plastic materials in practical engineering is gradually increasing due to its advantages of green ecology and waste utilization, and its response characteristics under earthquakes have attracted great attention. In this paper, seismic-resistant models, seismic-isolated models, and seismic-damped models for multistorey light steel-wood-plastic structures were established using the SAP2000 finite element software based on different seismic response methods. The seismic-isolated model is divided into five schemes, namely, LRB400, LRB500, LRB600, high damped, and friction pendulum-isolated bearings, and the seismic-damped model is divided into three schemes, namely, ordinary bracing, soft-steel bracing, and BRB bracing at the same locations around the 2nd floor of the building. Nonlinear time analysis was carried out for the nine schemes, comparing the period, structural interstorey displacement, base shear, top displacement, top acceleration, and economy of the structure under the action of an 8-degree earthquake. Results show that the period of the seismic-isolated system increased by approximately 130% compared to the seismic-resistant system, and the period of the damped system decreased slightly compared to the seismic system, the interstorey displacement, base shear, and top acceleration of both the seismic-isolated system and the damped system were smaller than those of the seismic-resistant system, and the seismic-isolated system decreased by approximately 40% compared to the damped system, and the seismic-isolated system was more effective than the damped system. From the comparison of postearthquake damage cost and full-cycle cost, the economic performance of the seismic-isolated structure is better than that of the damped and seismic-resistant structures. The conclusions of this paper can provide a scientific reference for promoting the use of new light steel-wood-plastic residential buildings.